Extraction and Analytical Characterization of Phenolic Compounds from Brazil Nut (Bertholletia excelsa) Skin Industrial by-Product - Vasquez-Rojas, Wilson Valerio; Hernández, Diego Martín; Cano, María Pilar; Reali, Tiziana Fornari (Trends in Sciences, 2023)
Pressurized liquid extraction (PLE) and ultrasound assisted extraction (UAE) were applied to extract phenolic antioxidants from defatted Brazil nut skin (DBNS) industrial by-product. Water/alcohol solvents (ethanol and methanol) (0 - 50 % v/v water) were used at temperatures of 50 - 200 °C in PLE and 50 °C was set in UAE. The effect on extraction yield, total phenolic compounds content (TPC), antioxidant capacity and phenolic characterization was determined. The temperature and water/alcohol mixture affected the dielectric constant, and this in turn influenced the yield, TPC, antioxidant activity and phenolic composition. In PLE, at 200 °C and 50 % (v/v) water/alcohol (ethanol and methanol) the highest yields (33.8 and 38.4 %, respectively), TPC (4673 and 5435 mg GAE/100 g DBNS) and antioxidant capacity (397 and 502 µmol TE/g DBNS) were obtained. Furthermore, at 50 °C, PLE had better extraction efficiency than UAE. Characterization of the extracts indicated that at 50 - 100 °C the extraction of protocatechuic acid and ellagic acid derivative were predominant, while at 150 - 200 °C catechin and vanillin derivatives stand out. In general, hydroxybenzoic acids and flavonoids were the most abundant phenolics, and the addition of 25 % v/v water to ethanol resulted in extracts with their highest concentration. Then, Brazil nut skin is an interesting phenolic-rich source with potential use to produce bioactive ingredients. HIGHLIGHTS High temperature and water/alcohol mixtures improves TPC and antioxidant capacity At given temperature, TPC values are linearly correlated with water/alcohol dielectric constant Extraction temperature modifies the abundance and profile of phenolic compounds Hydroxybenzoic acids and flavanols are predominant phenolics in Brazil nut skins At 50 °C, PLE have a better extraction efficiency of phenolic compounds than UAE GRAPHICAL ABSTRACT